Probing the Key Binding Sequence and Improvement of the Stability of a β‐Bungarotoxin‐binding Aptamer in Snake Venom. (22nd April 2016) - Ye, Fengping; Mi, Qili; Zhang, Ning; Li, Xuemei; Yu, Jing; Gao, Zhongping; Zheng, Ying; Fan, Quanshui; Wang, Jie; Wang, Jinglin
Abstract : Chemical modifications of the nucleotides can improve the stability of aptamers against enzyme degradation in serum, but it is not clear whether these methods are effective in snake venom. In this study, a DNA aptamer, βB‐1, which specifically recognize β‐bungarotoxin and Bungarus multicinctus venom was chosen, and the key binding sequence of the aptamer was determined. Based on the secondary structure of the truncated aptamer, locked nucleic acids and 2′‐O‐methyl nucleotides were applied to modify the stem and loop sequences, respectively. In addition, a 3′‐3′‐thymidine cap was also adopted to block the 3′ end. It was shown that these chemical modifications can all enhance the stability of the aptamer in snake venom. Simultaneously, modified aptamer with the above modifications in one sequence exhibited a significantly elevated biostability, with the half‐life improved from several minutes to 210 min while maintaining its binding affinity to the target. Abstract :